The Concept of Land Management by State-Owned Enterprises (SOE’s) - Indrawati, Yuli (JURNAL USM LAW REVIEW, 2025)
This study analyzes the concept of land management by State-Owned Enterprises (SOE's) based on the state's control and ownership rights over land. Based on the Constitution and Law No. 5 of 1960 concerning Basic Agrarian Principles (UUPA), land belongs to the Indonesian people, and the state only has the right to control it, except for land that is factually owned by the state, which gives it the right to own it. It is necessary to study more in depth regarding the state capital participation in SOE’s in the form of land, whether it arises from the right to control the state’s land or the right to own said land. The analysis was carried out using UUPA and regulations on state asset management. The novelty of this research lies in the distinction between state-controlled land and state-owned land in the context of capital participation in SOEs, which has not been clearly emphasized in previous studies. This study finds that only state-owned land, not merely state-controlled land, can be used for capital participation in SOEs due to the legal consequences of ownership transfer.